Stroll and walk, babble and talk : more about synonyms - Cleary, Brian P., 1959-; Gable, Brian, 1949- (Minneapolis, MN : Millbrook Press, 2008)
Rhyming text and illustrations present numerous examples of synonyms and their functions.
Wilson's Children, July 2009
Booklist, December 2008
Horn Book, April 2009
Kirkus Review, September 2008
3.7
3-6
Keywords: English language -- Synonyms and antonyms -- Juvenile literature; English language -- Synonyms and antonyms; English language -- Synonyms and antonyms